A Discourse of Mudawanah al-Usrah; Guaranteeing Women's Rights in Family Law Morocco's - Sheila Fakhria; Siti Marpuah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
Moroccan family code reform (mudawanah al-usrah) passed in 2004 after a long and dramatic process promoted by Moroccan women against retreating Islamists and male domination. This paper reviews Muslim family law (mudawanah al-usrah) in Marocco. Based on a literature research method that uses a normative juridical approach with a statutory approach, this paper aims to discuss the challenges and opportunities in guaranteeing women's rights in Moroccan family law. The study indicates that mudawanah al-usrah is a meeting point between Islamic rules and international conventions, providing a new identity for Moroccan society, especially women and their rights. This reform was also influenced by the Islamic feminist movement, which produced reforms to improve gender equality in Moroccan society. That was also expected to provide an overview of the protection of women's rights in family law, especially in Morocco, and become material for evaluation in its implementation in society. This study is also expected to be a reference for activists of family law studies to continue to develop the protection of women's rights in Islamic family law.